Effect of Foliar Fertilization by Two Types of Fertilizers on Growth and Yield of Cucumber (Omega Variety) under Protected Environment Conditions (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The experiment was conducted during the winter season in 2018 under a plastic house at Azawia- Babylon in (C.R.D) design with three replicates consisted of seven treatments such as a spray of foliar nutrition biomin 221with concentration 1‚1.25‚1.5  ml. liter-1 water and folic with concentration of 1‚1.5‚2  ml. litre-1 water, as well as a control treatment (without spraying) on cucumber plant (Omega variety), were grown in plastic house as follows three times ‚ The first spraying was conducted during flowering and the second spraying after two weeks of the first and the third after two weeks of the second. This study aims to determine the effect of foliar spray by nutritions biomin 221 and folic in growth and yield of cucumber planted in a plastic house. Results indicated that in vegetative growth characteristics (plant length, the number of leaves and dry weight of the shoot) and fruiting growth characteristics (fruit long, fruit weight ‚ the number of fruits.plant-1 and the one plant yield) in a spray of folicist with concentration 1.5 ml. litre-1  (323.7 cm ‚ 88.33 leaf ‚31.67 gm) of vegetative growth characteristics sequentially and (23.50 cm ‚113.85 gm‚43.03 fruit.plant-1 and 4.900 kg .plant-1) of fruiting growth characteristics sequentially and treatment of biomin 221 with concentration1.25 ml.litre-1 in vegetative growth characteristics (309.3cm‚70.33 leaf‚25.92gm) sequentially and fruiting growth characteristic (21.03cm‚111.01gm‚40.78 fruit.plant-1 and 4.523 kg.plant-1) sequentially